2013
DOI: 10.1111/bij.12171
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA recapitulates the cryptic mitochondrial lineages ofLumbricus rubellusand suggests the existence of cryptic species in an ecotoxological soil sentinel

Abstract: Mitochondrial DNA analysis has revealed two distinct phylogenetic lineages within the ecotoxological sentinel earthworm model Lumbricus rubellus Hoffmeister, 1843. The existence of these lineages could complicate ecotoxicological studies that use the species as a sentinel for soil contamination testing, as they may respond differently to contamination; however, as mitochondrial haplotypes are not always expected to segregate in the same way as chromosomal DNA in natural populations, we further investigated thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 70 publications
2
17
1
Order By: Relevance
“…The subtle intraspecific genetic variation shown within this species has been previously documented by King et al (2008) and Andre et al (2010) and our sequences clustered together with the described lineages A and B in these previous studies. Donnelly et al (2013) confirmed the lack of gene flow between these two lineages using microsatellite markers. Although RAD-Seq analyses revealed that certain European L. rubellus lineages may not be reproductively isolated (Giska et al, 2015), a similar genetic analysis observed that no hybridization occurs between A and B lineages in a number of UK locations where the lineages co-existed (Anderson pers.…”
Section: Cryptic Speciation In Lumbricus Rubellussupporting
confidence: 59%
“…The subtle intraspecific genetic variation shown within this species has been previously documented by King et al (2008) and Andre et al (2010) and our sequences clustered together with the described lineages A and B in these previous studies. Donnelly et al (2013) confirmed the lack of gene flow between these two lineages using microsatellite markers. Although RAD-Seq analyses revealed that certain European L. rubellus lineages may not be reproductively isolated (Giska et al, 2015), a similar genetic analysis observed that no hybridization occurs between A and B lineages in a number of UK locations where the lineages co-existed (Anderson pers.…”
Section: Cryptic Speciation In Lumbricus Rubellussupporting
confidence: 59%
“…This study shows that northern North American populations of the two earthworm species L. rubellus and L. terrestris share the same genetic lineages with populations of their native range in Europe. However, genetic diversity is lower in North America than in Europe, which is typical for invasive species (Sakai et al, ; Allendorf & Lundquist, ; King, Tibble, & Symondson, ; Gailing et al, ; Donnelly et al, ; Donnelly, Harper, Morgan, Pinto‐Juma, & Bruford, ; Giska et al, ). Consistent with studies in Europe, genetic diversity in L. rubellus was higher than in L. terrestris (King et al, 2008; Martinsson & Erséus, ), and intraspecific genetic distances of COI were comparable with those reported from Europe (King et al, 2008; James et al, ; Klarica, Kloss‐Brandstätter, Traugott, & Juen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Naughton et al (2014) found that microsatellite data support mtDNA lineages in Cenolia feather stars, although introgression was observed in a small number of individuals. In addition, Donnelly et al (2013) demonstrated support for mtDNA species in Lumbricus rubellus earthworms in South Wales. Interestingly though, divergent L. rubellus mtDNA lineages in Poland are not reproductively isolated (Giska et al, 2015).…”
Section: Introductionmentioning
confidence: 90%